Reconstruction of State Power Over Women's Bodies In The Mother and Child Welfare Law During The First Thousand Days of Life - Tomy Michael; Nadya Zerlinda Febrianti (Jurist-Diction, 2026)
In 2024, Indonesia made fundamental changes to improve the welfare of mothers and children. The enactment of Law of the Republic of Indonesia Number 4 of 2024 concerning the Welfare of Mothers and Children in the First Thousand Days of Life (Law No. 4/2024) provides special treatment for mothers and children. The philosophical basis of Law No. 4/2024 states that the state guarantees a prosperous life, both physically and spiritually, for every citizen, so as to improve the quality of life and welfare of all citizens, especially the welfare of mothers and children as mandated in the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). The method used is normative legal research. The existence of Law No. 4/2024 normatively provides protection for mothers and children, but contradictions arise. Law No. 4/2024 does not provide protection when the party intended to fulfill the rights does not carry out its obligations.